2022
DOI: 10.1111/1365-2745.13881
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the drivers of moss‐associated nitrogen fixation and cyanobacterial biomass in the eastern Canadian boreal forest

Abstract: Moss‐associated cyanobacteria nitrogen (N2‐) fixation can contribute to support moss growth and constitutes a major source of new N in boreal forest ecosystems. The biomass of moss‐colonizing cyanobacteria and their N2‐fixation are usually considered linearly correlated. Yet, recent evidence has shown that cyanobacterial biomass and N2‐fixation can be decoupled, suggesting that they are not necessary affected by the same environmental and ecological drivers. Climate and nutrients were reported as affecting mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 119 publications
4
22
0
Order By: Relevance
“…splendens and P . schreberi , consistent with findings in previous studies (DeLuca et al 2007 ; Stuart et al 2021a ; Liu and Rousk 2022 ; Renaudin et al 2022 ). While positive correlations between nitrogen fixation and relative abundances of bacteria other than cyanobacteria have been reported for some moss species (Holland-Moritz et al 2021 ), the strong correlation between the acetylene reduction rate and the rate of cyanobacterial colonization in this study suggests that cyanobacteria contribute to nitrogen fixation on moss carpets in subalpine forest of Mt.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…splendens and P . schreberi , consistent with findings in previous studies (DeLuca et al 2007 ; Stuart et al 2021a ; Liu and Rousk 2022 ; Renaudin et al 2022 ). While positive correlations between nitrogen fixation and relative abundances of bacteria other than cyanobacteria have been reported for some moss species (Holland-Moritz et al 2021 ), the strong correlation between the acetylene reduction rate and the rate of cyanobacterial colonization in this study suggests that cyanobacteria contribute to nitrogen fixation on moss carpets in subalpine forest of Mt.…”
Section: Discussionsupporting
confidence: 92%
“…Fallen logs, as coarse woody debris, can be a source of nutrients such as phosphorus as they decompose (Laiho and Prescott 2004 ; Brais et al 2006 ). Cases of phosphorus promoting cyanobacterial biomass (Renaudin et al 2022 ) and acetylene reduction (Zackrisson et al 2004 ) have been reported. This result may be due to the greater P supply from decayed fallen logs than from the ground surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green section is thought to be photosynthetically active and is often in focus when studying bacterial communities associated with mosses. The green section is also associated with nitrogen fixing cyanobacteria (Renaudin et al, 2022a). Meanwhile, microbial communities associated with brown sections are much less studied, even though they are hypothesized to be an important source of nutrients for certain bacterial taxa (Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacterial N 2 fixation within feather-moss communities is a primary source of new nitrogen (N) in boreal forest ecosystems (DeLuca et al, 2002a, DeLuca et al, 2002bZackrisson et al, 2004;DeLuca et al, 2008;Renaudin et al, 2022a, Renaudin et al, 2022b; however, understanding of how this N source influences key ecosystem processes (e.g. productivity, biodiversity and carbon [C] cycling) remains limited with the precise cellular mechanisms yet to be defined.…”
Section: Introductionmentioning
confidence: 99%